Comparison of physical activity and sedentary behavior levels in secondary and university students - Natalie Naidoo; Oladapo Michael Olagbegi; Thayananthee Nadasan; Joshua Oluwafisayo Afolabi (Universidade Federal do Ceará, 2022)
Objective: to compare physical activity and sedentary behavior in university students and secondary students. Methods: the cross-sectional study involved 202 selected secondary students and 171 university students. The Global Physical Activity Questionnaire was administered to the respondents. Percentages, chi-square test, Mann Whitney U test and linear regression were used for data analysis. Results: about 63% and 32% of secondary and university students, respectively, reported high levels of physical activity, while 84.7% and 71.9% of secondary and undergraduate students, respectively, met guidelines for sedentary behavior. The secondary students had significantly higher scores than the university students in vigorous (p=0.004), moderate (p<0.001), and total physical activity (p<0.001). The observed difference was more prominent among females. Conclusion: secondary students had higher scores of physical activity and spent less time in sedentary behavior.